Narrative inquiry on tensions lived by a high school teacher in the process of curriculum making - Diego Martín Alonso; Nieves Blanco García; J. Eduardo Sierra Nieto (Arizona State University, 2018)
In this article we delve into tensions lived by teachers when there is no coincidence between intentions and desires of curricular plan and lived experience. By means of a narrative inquiry we go deep on a high school teacher´s experience and we pause in a short time period in which he lived a disagreement with the educational inspection and the official curriculum. Later, through an exegetical analysis, we relate the teacher´s story with the scientific literature, in order to open new questions and thoughts that help to live tensions in a fruitful way. The analysis points out to three dimensions where tensions are lived: needs, language and time. Finally, the study of these tensions shows that their origin is located in an epistemological framework. It means, they are the result of a friction between different educational knowledge perspectives, which turn out to be different ways of dealing with planning and teacher work.